2022
DOI: 10.1186/s40249-022-00961-5
|View full text |Cite
|
Sign up to set email alerts
|

Infection fatality rate and infection attack rate of COVID-19 in South American countries

Abstract: Background The ongoing COVID-19 pandemic hit South America badly with multiple waves. Different COVID-19 variants have been storming across the region, leading to more severe infections and deaths even in places with high vaccination coverage. This study aims to assess the spatiotemporal variability of the COVID-19 pandemic and estimate the infection fatality rate (IFR), infection attack rate (IAR) and reproduction number ($${R}_{0}$$ R … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…The model formulation used here is an elaboration of the conventional SEIRV epidemic population model where the variables S, E, I, R and V (k) denote the number of individuals in the PLOS GLOBAL PUBLIC HEALTH Susceptible, Exposed, Infectious, Recovered and Vaccinated groups [31,32]. Susceptible individuals flow through the compartments in linear order: S!E!I!R.…”
Section: Modelmentioning
confidence: 99%
“…The model formulation used here is an elaboration of the conventional SEIRV epidemic population model where the variables S, E, I, R and V (k) denote the number of individuals in the PLOS GLOBAL PUBLIC HEALTH Susceptible, Exposed, Infectious, Recovered and Vaccinated groups [31,32]. Susceptible individuals flow through the compartments in linear order: S!E!I!R.…”
Section: Modelmentioning
confidence: 99%
“…An interesting finding was found in a study within the USA. The study suggested that mortality in urban region of the USA is higher than that of rural area[12]. Another study has suggested that air quality, demographics, global interconnectedness, urbanization trends, historic trends in health expenditure and policy measure for covid-19 mitigation have influence on mortality difference in EU countries[13].…”
Section: Resultsmentioning
confidence: 99%
“…Chang, S et al used a SEIR transmission model to simulate the spread of SARS-CoV-2 in ten major U.S. cities and concluded that mobility-related mechanisms lead to economic losses and increased infection rates(26). Musa, SS et al used a dynamic model of COVID-19 to simulate the rate of transmission, and the magnitude of mortality under different parameters and concluded that a two-pronged approach of maintaining social distance and vaccination could reduce the mortality caused by COVID-19 in South America (27).…”
Section: Literature Reviewmentioning
confidence: 99%